2020
DOI: 10.1653/024.103.0206
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of First Instar Hippodamia convergens (Coleoptera: Coccinellidae) and Chrysoperla rufilabris (Neuroptera: Chrysopidae) to the Insecticide Sulfoxaflor

Abstract: The soybean aphid, Aphis glycines Matsumura (Hemiptera: Aphididae), continues to be the most economically important arthropod pest of soybean in the Midwest. Currently, management tactics for A. glycines rely on scouting and application of broad-spectrum insecticides. However, broadspectrum insecticides are toxic to most natural enemies of this aphid. Selective insecticides may provide an alternative strategy for suppressing A. glycines populations while conserving populations of its natural enemies. Therefore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…This result is in agreement with another study 45 that reported how cypermethrin caused an extension in the larval developmental time of different coccinellids. Also, other authors observed that λ‐cyhalothrin increased the developmental time of the 1 st and 2 nd larval instars of Chrysoperla rufilabris (Burmeister) (Neuroptera:Chrysopidae) 61 and deltamethrin lengthened the developmental time of 4 th instar larvae of Ceratomegilla undecimnotata (Schneider) (Coleoptera: Coccinellidae) 62 …”
Section: Discussionmentioning
confidence: 97%
“…This result is in agreement with another study 45 that reported how cypermethrin caused an extension in the larval developmental time of different coccinellids. Also, other authors observed that λ‐cyhalothrin increased the developmental time of the 1 st and 2 nd larval instars of Chrysoperla rufilabris (Burmeister) (Neuroptera:Chrysopidae) 61 and deltamethrin lengthened the developmental time of 4 th instar larvae of Ceratomegilla undecimnotata (Schneider) (Coleoptera: Coccinellidae) 62 …”
Section: Discussionmentioning
confidence: 97%
“…per insect significantly extended the duration of larval and pupal stages of H. variegata . Extended preadult developmental time has been found in many aphid predators, such as H. axyridis [ 28 ], Chrysoperla rufilabris (Neuroptera: Chrysopidae) [ 33 ], and C. carnea [ 34 ] after treatment with sulfoxaflor. These findings can be explained either by the antifeeding effect of sulfoxaflor on coccinellid predators [ 35 ] and the consequent reduced food intake or by the fact that affected larvae may use their metabolic energy for sulfoxaflor detoxification at expenses of their development and growth [ 10 , 32 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sulfoxaflor was also toxic to T. japonicus in the first experiment (i.e., residual contact toxicity) with mean mortality of 55% (Figure 1). Sulfoxaflor is generally described as an insecticide with relatively low toxicity to predators (46)(47)(48), but higher toxicity to pollinators (47) and some parasitoids (49,50). Contrary to the first experiment (i.e., residual contact toxicity), the residual contact toxicity of sulfoxaflor (mortality <25%) was similar to that of pyrethrins, azadirachtin + pyrethrins, and clothianidin in the last experiment (i.e., different routes of exposure) (Figure 5A).…”
Section: Discussionmentioning
confidence: 99%